MENINGKATKAN KEMAMPUAN PENGUASAAN KOSA KATA BAHASA INGGRIS SISWA KELAS VII B MTs NEGERI 2 TANAH LAUT MELALUI PENERAPAN METODE PERMAINAN TEBAK KATA (PETAKA) TAHUN PELAJARAN 2018/2019 - Norhidayah Norhidayah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
English is one of the subjects that is taught at every grade level in schools, especially at the elementary level of junior secondary education (SMP/MTs). One level of education that also carries out English language learning is in public/private MTs from grade VII to grade IX. A lot of English subject matter is presented at every grade level, one of the materials taught is about the linguistic element in English, namely English vocabulary. Especially in class VII Madrasah Tsanawiyah, discussion material on elements of vocabulary is presented, which aims to make students able to master as much vocabulary as possible in English. In addition to mastering English vocabulary, its forms, meanings and usage rules, it is hoped that students can also apply them in daily communication in English, both in spoken and written language. To achieve this goal, of course, students need to be equipped with maximum English vocabulary mastery. Among them what needs to be done is through training and teaching English in schools by applying various appropriate and appropriate learning techniques and methods. One of the appropriate learning techniques in learning English, especially those related to efforts to improve the ability to master English vocabulary is the Guessing Game Technique (PETAKA). The Guessing Game Technique is an English learning method that is structured based on the pattern of learning while playing in the use of English vocabulary. The way the game is played is to use guessing cards that contain certain statements that students have to guess the meaning of with a certain word as well. This English guessing game technique turned out to be enough to get a response and attention from the students in the learning process. In the pre-cycle researchers still use conventional methods in learning, students who complete learning in the pre-cycle only 21 students or 60% of students who complete learning. Then in cycle 1 the researchers made improvements to learning by starting to apply the Guessing Game Method. The result is that in cycle 1, the number of students who completed learning increased to 27 students or 77% of students were able to complete learning. In cycle 2 the researchers still use the same method, namely the guessing game method in the teaching and learning process, in cycle 2 there is an increase in the number of students who have completed learning to 33 students or 94% of students are able to complete learning. The conclusion from the results of research conducted in Class VII B MTs Negeri 2 Tanah Laut for the 2018/2019 academic year, which is in a period of approximately 3 weeks, with the concept of 4X meetings, the English word guessing game method has a positive impact on the process of improving vocabulary mastery skills. English for students in Class VII B of MTs Negeri 2 Tanah Laut for the 2018/2019 academic year.